Investigation Into the Predictive Potential of Three-Dimensional Ultrasonographic Placental Volume and Vascular Indices in Gestational Diabetes Mellitus - Han, Zhenyan; Zhang, Yuan; Li, Xuelan; Chiu, Wei-Hsiu; Yin, Yuzhu; Hou, Hongying (Frontiers in Endocrinology, 2021)
Background: The use of ultrasonography in pregnancies complicated with gestational diabetes mellitus (GDM) can vary according to clinical practice. This study aims to compare the changes of placental volume (PV) and vascular indices measured by three-dimensional (3D) Power Doppler between pregnant women with and without GDM. Materials and methods: This was a prospective study of singleton pregnancies who took the early nuchal translucency examination from January 2018 to September 2019. Data on PV and vascular indices including vascularization index (VI), flow index (FI), and vascularization flow index (VFI) between pregnant women with and without GDM were measured by 3D Power Doppler ultrasound machine. Univariate and multivariate logistic regression determined the association between risk factors and GDM. Receiver operating characteristic (ROC) and area under the ROC curve (AUC) were applied to evaluate the diagnostic value of different parameters for GDM. Results: Of the 141 pregnant women enrolled, 35 developed GDM and 106 did not. The maternal age and gravida in the GDM group were significantly higher than that in the non-GDM group. The PV, VI, FI and VFI in the GDM group were significantly lower than that in the non-GDM group. There were no significant differences in other clinical parameters between the two groups. After adjustments in multivariate logistic regression analysis, significant differences were observed in VI (odds ratio (OR) = 0.98, 95% confidence interval (CI) = 0.951-1.002), FI (OR = 0.93, 955 CI: 0.86-1.00) and VFI (OR = 0.67, 95% CI = 0.52-0.87). ROC analysis indicated that the combination of maternal age, gravida, PV and VFI was more accurate as a marker for detecting GDM than the PV, VI, FI or VFI alone. Conclusions: The 3D ultrasonography results suggest that PV and vascular indices (VI, FI and VFI) during the first trimester may serve as potential markers for GDM diagnosis. The combination of maternal age, gravida and sonographic markers may have good diagnostic values for GDM, which should be confirmed by further investigations.